2021
DOI: 10.1519/jsc.0000000000003190
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses and Time-Motion Analysis of Kickboxing: Differences Between Full Contact, Light Contact, and Point Fighting Contests

Abstract: This study investigated the physiological responses and time structure of kickboxing styles (full contact, light contact, and point fighting). Blood lactate [La] before and after combats, mean heart rate (HRmean), percentage of time spent in HR zones, and rating of perceived exertion were assessed. Time spent in high-intensity activities (HIAs), low-intensity activities (LIAs), and referee pauses (P) were recorded according to rounds (R) and kickboxing styles. [La] increased statistically significant after kic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…It was observed that kickboxers experienced higher physiological stress and lower work outputs during consecutive rounds (Salci, 2015). Ouergui et al (2019) observed a similar effect in their study. They recorded the highest increase in HR in the first round of the fight and the same increase in the third round.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It was observed that kickboxers experienced higher physiological stress and lower work outputs during consecutive rounds (Salci, 2015). Ouergui et al (2019) observed a similar effect in their study. They recorded the highest increase in HR in the first round of the fight and the same increase in the third round.…”
Section: Discussionsupporting
confidence: 60%
“…Most studies of kickboxers have been based on full-contact competitions, where, according to the rules, low kicks and knee strikes are not allowed. Previous studies have dealt with the physique of athletes, physiological responses, and time-motion and technical-tactical analyses in kickboxing athletes during simulated fights and training (Ouergui et al, 2013a(Ouergui et al, , 2014b(Ouergui et al, , 2016(Ouergui et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a higher level of aerobic endurance is needed. Other studies have indicated that the mean VO 2 peak in elite kickboxers ranged from 54 to 69 mL/kg/min [ 56 , 57 ], while in the judo athletes, it was 53.75 mL/kg/min [ 58 ]. Comparison of the results of our research to these findings reveals that in the present study, ju-jitsu athletes had a lower level of aerobic capacity than the world’s elite kickboxers and judo athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The repetitive performance of these techniques requires high physical and physiological demands [ 1 , 4 ]. As such, the main goal of kickboxing training is to prepare the kickboxers to effectively manage both the technical/tactical [ 3 ] and the physical/physiological [ 5 , 6 ] demands of the combat.…”
Section: Introductionmentioning
confidence: 99%